Breve historia de la prosa completa de Quevedo (1648-2020) - Rey, Alfonso (El Colegio de México, 2023)
In addition to his well known poetry, Quevedo produced an extensive number of prose works, ranging from short narratives to extensive treatises. He held very clear ethical, political and aesthetic convictions, and in order to understand his thought, his varied prose work has to be considered as an integrated whole. The present text offers a brief survey of his complete prose works in editions from 1648 through to 2020.